DEVELOPMENT OF LAND MOISTURE ESTIMATION MODEL USING MODIS INFRARED, THERMAL, AND EVI TO DETECT DROUGHT AT PADDY FIELD - Dede Dirgahayu Domiri (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2013)
The drought phenomena often occurs in summer season at paddy field of Java island. The drought phenomena causes decrease in rice production. This research was aimed to develop a model of land  moisture (LM) estimation  at  agricultural field,  especially  for  paddy  field  based  on Moderate Resolution Imaging Spectroradiometer (MODIS) satellite data which has seven reflectance and two thermal bands. The method used in this study included data correction, advance processing of MODIS data  (land indices  transformation),  extraction  of  land  indices  value  at  location  of  field  survey,  and regression  analysis  to  make  the  best  model  of  land  moisture  estimation. The  result  showed that reflectance of 2nd channel (NIR) and rasio of Enhanced Vegetation Index (EVI) with Land Surface Temperature (LST) had high correlation with surface soil moisture (% weight) at 0 – 20 cm depth with formula: LM = 15.9*EVI/LST – 0.934*R2 – 16.8 (SE=9.6%; R2 =76.2%). Based on the model, land  moisture  was  derived  spatially at the  agricultural field,  especially at paddy  field to  detect  andmonitor drought events. Information of land moisture can be used as an indicator to detect drought condition and early growing season of paddy crop